PERCEPTIONS OF MIDDLE SCHOOL STUDENTS AND TEACHERS ON RULES - Scandelai Parra, Andressa Carolina; Nogueira da Cruz, Luciana Aparecida [UNESP] (Fundacao Univ Tocantins, 2021)
Jean Piaget's studies of child moral development in the 1930 already explained the importance of children's participation in building rules for the development of morality. Our objective was to investigate the perceptions of 1,031 students and 58 teachers in the final years of middle school in four public schools, regarding these school rules. The general objective was to investigate the participation of the students in the elaboration, compliance and knowledge of the rules. The adopted method was descriptive, and the data's nature is quantitative and correlational. The instruments are questionnaires composed of items that assess the subjects' perceptions about dimensions that constitute the school climate. To achieve the objective, we stick to some items of dimension Rules, sanctions and safety at school of the instrument. We conclude by analyzing the results that the investigated schools rarely allow the participation of the students in the elaboration of the rules, consequently they do not understand and do not comply with them.
Keywords: Rules; Sociomoral Environment; Moral Development